Determination of Blood Culture Contamination Rate at a Tertiary Care Hospital - Naqvi, Sakeenah Hussain; Aiman, Eisha; Mirza, Irfan Ali (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine bacterial contamination rates in blood culture specimens received at Microbiology Department, Armed Forces Institute of Pathology, Rawalpindi Pakistan.Study Design: Cross-sectional study.Place & Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology & Combined Military Hospital, Rawalpindi Pakistan, from Aug to Dec 2022.Methodology: All the blood culture samples signaled positive on automated blood culture system, were sub cultured on appropriate media for identification of isolates. The skin flora was labeled as contaminant, if fulfilled the criteria as per operational definition. The clinical history and other required data was incorporated in Excel sheet and was analyzed.Results: The total number of blood cultures received was 1816, of which 425 were signaled positive by the system. Of the total blood cultures, 260(14%) were identified as contaminants including Coagulase negative Staphylococcus (83.%), Corynebacterium spp. (10.4%), Bacillus spp. (4.2%) and Micrococcus (2.3%). These organisms were identified as contaminants after thorough evaluation of the clinical condition of the patients. The highest blood culture contamination rate (23%) was observed in samples received from neonatal Intensive Care Unit (ICU), followed by paediatric ICU& paediatric wards.Conclusion:  In our study the overall blood culture contamination rates are found to be higher than internationally accepted rate with the highest contamination rates are found to be in the neonatal ICU and paediatric wards. Therefore, comprehensive plan of training the relevant healthcare workers (HCW) is recommended with strict monitoring to minimize the blood culture contamination rate to the internationally acceptable level.